GaN-Based Laser Diodes Towards Longer Wavelengths and Short Pulses - Scheibenzuber, Wolfgang G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The emergence of highly efficient short-wavelength laser diodes based on the III-V compound semiconductor GaN has not only enabled high-density optical data storage, but is also expected to revolutionize display applications. Moreover, a variety of scientific applications in biophotonics, materials research and quantum optics can benefit from these versatile and cost-efficient laser light sources in the near-UV to green spectral range. This thesis describes the device physics of GaN-based laser diodes, together with recent efforts to achieve longer emission wavelengths and short-pulse emission. Experimental and theoretical approaches are employed to address the individual device properties and optimize the laser diodes toward the requirements of specific applications.
Basic Concepts -- Thermal Properties -- Light Propagation and Amplification in Laser Diodes from Violet to Green -- Semipolar Crystal Orientations for Green Laser Diodes -- Dynamics of Charge Carriers and Photons -- Short-Pulse Laser Diodes.
Keywords: Physics; Physics; Laser Technology, Photonics; Semiconductors; Optics, Optoelectronics, Plasmonics and Optical Devices